Randomized, Controlled Trial of an Advance Care Planning Video Decision Support Tool for Patients With Advanced Heart Failure. Issue 1 (5th July 2016) - El-Jawahri, Areej; Paasche-Orlow, Michael K.; Matlock, Dan; Stevenson, Lynne Warner; Lewis, Eldrin F.; Stewart, Garrick; Semigran, Marc; Chang, Yuchiao; Parks, Kimberly; Walker-Corkery, Elizabeth S.; Temel, Jennifer S.; Bohossian, Hacho; et al.
Abstract : BACKGROUND: Conversations about goals of care and cardiopulmonary resuscitation (CPR)/intubation for patients with advanced heart failure can be difficult. This study examined the impact of a video decision support tool and patient checklist on advance care planning for patients with heart failure. METHODS: This was a multisite, randomized, controlled trial of a video-assisted intervention and advance care planning checklist versus a verbal description in 246 patients ≥64 years of age with heart failure and an estimated likelihood of death of >50% within 2 years. Intervention participants received a verbal description for goals of care (life-prolonging care, limited care, and comfort care) and CPR/intubation plus a 6-minute video depicting the 3 levels of care, CPR/intubation, and an advance care planning checklist. Control subjects received only the verbal description. The primary analysis compared the proportion of patients preferring comfort care between study arms immediately after the intervention. Secondary outcomes were CPR/intubation preferences and knowledge (6-item test; range, 0–6) after intervention. RESULTS: In the intervention group, 27 (22%) chose life-prolonging care, 31 (25%) chose limited care, 63 (51%) selected comfort care, and 2 (2%) were uncertain. In the control group, 50 (41%) chose life-prolonging care, 27 (22%) selected limited care, 37 (30%) chose comfort care, and 8 (7%) were uncertain ( P <0.001). Intervention participants (compared with control subjects) were more likely to forgo CPR (68% versus 35%; P <0.001) and intubation (77% versus 48%; P <0.001) and had higher mean knowledge scores (4.1 versus 3.0; P <0.001). CONCLUSIONS: Patients with heart failure who viewed a video were more informed, more likely to select a focus on comfort, and less likely to desire CPR/intubation compared with patients receiving verbal information only. CLINICAL TRIAL REGISTRATION: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01589120. Abstract : Supplemental Digital Content is available in the text.